Evaluation of New Polish Articulation Lists (NAL-93) in the Presence of Various Speech-Like Maskers - Anna SCHELENZ; Ewa SKRODZKA (Archives of Acoustics)
The main goal of the research was to obtain a set of data for ability of speech in noise recognition using Polish word test (New Articulation Lists – NAL-93) with two different masking signals. The attempt was also made to standardise the background noise for Polish speech tests by creating babble noise for NAL-93. Two types of background noise were used for Polish word test – the babble noise and the speech noise. The short method was chosen in the study as it provided similar results to constant stimuli method using less word material. The experiment using both maskers was presented to 10 listeners with normal hearing.